2016
DOI: 10.4103/2249-4863.192323
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disease control and co-existing risk factors on heart rate variability in Gujarati type 2 diabetics: An observational study

Abstract: Background:Type 2 diabetes mellitus (T2DM) is a proven threat of cardiac dysautonomia with paucity of studies from India. Poor disease control makes it further worse with co-existence of hypertension in majority. Heart rate variability (HRV) is a validated noninvasive tool to assess cardiac autonomic status.Aim:We studied HRV parameters of type 2 diabetics looking for effects of disease control and other co-existing risk factors.Materials and Methods:Ninety-eight hypertensive and forty normotensive under–treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(38 reference statements)
2
5
1
Order By: Relevance
“…LF/HF ratio denotes sympatho-vagal balance, and an increase signifies sympathetic dominance which could result from either damage to cardiac autonomic nerves by hyperglycemia in T2DM or by the sympathetic overactivity as seen in HTN. Findings of Solanki et al 44 , 45 were in contrast to those of previous studies, where they reported no significant effect of HTN on autonomic function in T2DM. However, they did not include healthy controls or a euglycemic hypertensive group which makes it difficult to compare it with the results of the present study.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…LF/HF ratio denotes sympatho-vagal balance, and an increase signifies sympathetic dominance which could result from either damage to cardiac autonomic nerves by hyperglycemia in T2DM or by the sympathetic overactivity as seen in HTN. Findings of Solanki et al 44 , 45 were in contrast to those of previous studies, where they reported no significant effect of HTN on autonomic function in T2DM. However, they did not include healthy controls or a euglycemic hypertensive group which makes it difficult to compare it with the results of the present study.…”
Section: Discussioncontrasting
confidence: 85%
“…More recently, Istenes et al 14 assessed resting HRV using the frequency domain measures and found an additive effect of HTN on impaired autonomic function in diabetic patients. However, Solanki et al 44 , 45 found non-significant difference in HRV parameters (frequency domain, time domain and non-linear measures) between diabetics with optimal vs. poor BP control. They recorded no difference in the overall HRV except for LF/HF ratio, which was found to be lower in the hypertensive diabetics.…”
Section: Discussionmentioning
confidence: 97%
“…This is followed by breathlessness (28%) and nausea/vomiting (24%) as seen in Gupta, et al study [19,20]. Incidence of nausea and vomiting is reported by Ghanshyam, et al [14] and Solanki [21] which matches with current study.…”
Section: Discussionsupporting
confidence: 88%
“…We found the same scenario in diabetics with than without antihypertensives in our previous studies on various cardiovascular parameters. [32021] 4) We did matching of subgroups by age and gender, and other confounders were also comparable, which was not the case in many other studies, 5) glycemic control was poor in most diabetics alike our previous studies[352021] and that overshadows other risk factors, 6) both BH and CH were measured simultaneously by same device, which is not so in tonometry-based devices,[22] which are used in most studies. 7) It was a cross-sectional design with moderate sample as opposed to vertical studies with large sample.…”
Section: Discussionmentioning
confidence: 99%